The promise of Francis : the man, the pope, and the challenge of change - Willey, David (Gallery original nonfiction hardcover, 2015)
"With more than four decades of firsthand experience reporting from Vatican City, David Willey explores the religious and personal background of Pope Francis and his ability to fulfill the promises of reform made during the first two years of his papacy"--